(untitled) (Vietnam Journal of Community Medicine, 2022)
The results of the study on the current state of health of production workers directly at the AC Dong Anh roofing factory (Dong Anh Investment, Construction and Construction Materials Joint Stock Company) show that: mainly healthy type II and III accounted for 79.4%, type 4 accounted for 11.6%, no healthy type V. The main diseases were molar, ear-nose-throat, eyes. ... In addition, the decline in lung function through examination and detection of occupational diseases shows that the rate of change in lung ventilation function in workers increases with age and occupation; The main form of change is mild restrictive syndrome (94.1%), the degree of change is mainly mild (70.8%).